Growth and Yield Response of Selected Aman Varieties as Influenced by Leaf Cutting (Bangladesh Agronomy Journal, 2023)
Sustainable crop production in the era of increasing input price is adding extra burden while the cultivable land is reducing at an alarming pace. This research article aims to test the hypothesis that the leaf cutting as an agronomic practice could be a better prospective in increasing rice grain production. An experiment was carried out in the experimental field of Sher-e-Bangla Agricultural University, to assess the effect of leaf cutting on plant growth and yield of selected BRRI released Aman varieties. The experiment consisted of five rice varieties namely BRRI dhan32, BRRI dhan33, BRRI dhan39, BRRI dhan62, and BRRI dhan56 treated either as control or leaf cutting (except flag and penultimate leaf). The experiment was laid out in randomized complete block design (RCBD) with three replicates. Leaf cutting was observed with detrimental effect on the usual plant growth and yield performances. Irrespective of all studied varieties, the highest value was obtained while no leaf cutting was performed. BRRI dhan39 was found to be the highest yield producing variety in terms of greater flag leaf length, leaf breadth, flag leaf area, required less time to grain filling, filled grain panicle-1, filled grain%, 1000-grain weight, grain yield and harvest index in leaf cutting condition followed by BRRI dhan32 in terms of plant height, chlorophyll content, tiller hill-1 and straw yield. No significant differences in yield contributing parameters except the panicle hill-1 were observed in leaf cutting condition compared to control. Leaf cutting at heading (except flag leaf and penultimate leaves) reduced average 10-20% loss of grain yield. BRRI dhan62 shown highly affected by leaf cutting compared to the rest other varieties. Therefore, it can be concluded by suggesting that leaf cutting reduces plant functional efficiency which can be improved by enhancing photosynthetic capacity through proper management of leaf architecture.Bangladesh Agron. J. 2022, 25(2): 1-9